Antibiotic Cocktail for Pediatric Acute Severe Colitis and the Microbiome: The PRASCO Randomized Controlled Trial. Issue 11 (November 2020) - Turner, Dan; Bishai, Jason; Reshef, Leah; Abitbol, Guila; Focht, Gili; Marcus, Dana; Ledder, Oren; Lev‐Tzion, Raffi; Orlanski‐Meyer, Esther; Yerushalmi, Baruch; Aloi, Marina; Griffiths, Anne M.; et al.
Abstract : Background: : Alterations in the microbiome have been postulated to drive inflammation in IBD. In this pilot randomized controlled trial, we evaluated the effectiveness of quadruple antibiotic cocktail in addition to intravenous‐corticosteroids (IVCSs) in acute severe colitis (ASC). Methods: : Hospitalized children with ASC (pediatric ulcerative colitis activity index [PUCAI] ≥65) were randomized into 2 arms: the first received antibiotics in addition to IVCS (amoxicillin, vancomycin, metronidazole, doxycycline/ciprofloxacin [IVCS+AB]), whereas the other received only IVCS for 14 days. The primary outcome was disease activity (PUCAI) at day 5. Microbiome was analyzed using 16S rRNA gene and metagenome. Results: : Twenty‐eight children were included: 16 in the AB + IVCS arm and 12 in the IVCS arm (mean age 13.9 ± 4.1 years and 23 [82%] with extensive colitis). The mean day‐5 PUCAI was 25 ± 16.7 vs 40.4 ± 20.4, respectively ( P = 0.037). Only 3 and 2 children, respectively, required colectomy during 1‐year follow‐up ( P = 0.89). Microbiome data at time of admission were analyzed for 25 children, of whom 17 (68%) had a predominant bacterial species (>33% abundance); response was not associated with the specific species, whereas decreased microbiome diversity at admission was associated with day‐5 response in the IVCS arm. Conclusion: : Patients with ASC have alterations in the microbiome characterized by loss of diversity and presence of predominant bacterial species. Quadruple therapy in addition to IVCS improved disease activity on day 5, but larger studies are needed to determine whether this is associated with improved long‐term outcomes (clinicaltrials.gov NCT02033408).